Recent trends in studying of alcohol-induced liver disease - I. I. Komkova; M. S. Zharkova; M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze main epidemiologic tendencies of development of alcoholic liver disease, mechanisms of its development, mortality in this population of patients. To discuss an option of new targets for treatment of this disease.Original positions. Alcohol abuse is the third leading cause of morbidity and mortality in the young age. In the studies it was demonstrated, that there is significant difference in death rate of liver cirrhosis between European countries. Disease risk factors include: amount of taken alcohol, its type, frequency of use, female gender, excessive body weight. Besides damaging effect, in response to admission of alcohol processes of protection and neogenesis of the liver through activation of IL-6, IL-22 receptors, STAT-proteins system are initiated. Mechanism of TNFα action, resulting in apoptosis of hepatocytes through activation of acidic sphingomyelinase is investigated.Conclusion. Application of acidic sphingomyelinase, influence on Kupffer's cells phenotype, cannabinoids receptors as new targets for treatment of alcoholic liver disease is possible. At treatment of patients with severe alcohol-induced hepatitis corticosteroids considerably increasing 28-day's survival rate are actively applied. To increase efficacy of treatment of acute alcoholic hepatitis the issue of addition to standard treatment by glucocorticosteroids IL-22 is taken into account.